Mapping the Mission Statements of U.S. LCME-Accredited Medical Schools: An Exploration of Organizational Communalities. (May 2019) - Hafferty, Frederic W.; Grbic, Douglas; Hafferty, Philip K.
Abstract : Purpose: Mission statements (MSs) express an organization's purpose and reflect the broader social environment in which they function. The authors analyze MS text to explore how medical schools can be relationally viewed and how particular thematic narratives within MSs can be deployed to associate schools in hithertofore unexplored ways. Method: The authors analyzed the MSs (as of 1/1/2017) of 144 U.S. Liaison Committee on Medical Education–accredited schools. Using schools as their unit of analysis, they coded MSs using 44 themes. They employed content analysis to identify themes within MSs, factor analysis to identify core thematic dimensions embedded in MSs, and network analysis to examine relationships among schools based on these thematic dimensions. The authors used four standard school characteristics to examine the validity of their results. Results: Content analysis revealed 20 core themes. Factor analysis identified four thematic dimensions: Primary Care/Diversity; Future Learning–External; Traditional; and Learning Environment–Internal. Based on the 20 core themes and using the MSs of 125 schools with nonextreme MS code counts, the authors found that schools form a complete network, and that schools form distinctive network-based clusters based on the identified factors. The four thematic dimensions were significantly differentiated across the four standard school characteristics. Conclusions: The authors found distinctive patterns of MS linkages among schools along with thematic linkages within MS themes, supporting the contentions that medical schools can be both differentiated and connected based on their MSs and that understanding MS content must move beyond simple frequency counts of MS attributes. Abstract : Supplemental Digital Content is available in the text.